Pengaruh Green Accounting dan Profitabilitas Terhadap Nilai Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2020-2024 - Paizer Turrahman; Suwarno Suwarno; Eri Triharyati; Dewi Anggraini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of Green Accounting and Profitability on Firm Value in mining companies listed on the Indonesia Stock Exchange for the 2020-2024 period over 5 years. The sampling technique used purposive sampling, resulting in a total sample of 48 observation companies. The data used is secondary data obtained from the Indonesia Stock Exchange website and each respective company. The analysis method used in this study is panel data regression. This study uses Eviews 13. The results of this study indicate that: Green Accounting has no significant effect on Company Value; Profitability has no significant effect on Company Value; Green Accounting and Profitability no Company Value have a significant positive effect on Company Value, Recommendations regarding the Effect of Green Accounting and Profitability on the Value of Mining Companies listed on the Indonesia Stock Exchange. The importance of Companies disclosing environmental costs and managing assets in order to obtain greater profits to provide good hope for company sustainability.